Cultural evolution - Feldman, Marcus (Henry Stewart Talks, 2007)
Culture definition, Analogies between genes and culture, An example of cultural mutation, Vertical cultural transmission, Case studies, Selection with vertical transmission, The "Kuru" model, Transmission in models with three semes, Oblique transmission, Horizontal transmission, Rates of change, Cultural niche construction in vertical transmission rates, Constraints on cultural variation, Culture and its effect on genes, Quantification of genetic and cultural spread